Plastics and sustainability : grey is the new green : exploring the nuances and complexities of modern plastics - Tolinski, Michael; Carlin, Conor P. (John Wiley & Sons, Inc., 2021)
"For the 2nd edition, it was most important to provide current data and references due to the number and magnitude of changes in the plastics industry since the 1st edition. Some industry publications are the same as what was used before (Plastics News, Plastics Engineering, etc.) and access to academic journals allowed for exploration into today's research. The creation and launch of new multinational consortia, e.g. Ellen MacArthur Foundation, Circular Economy, Closed Loop Partners, etc. has led to increased investment in specific technologies as well as new data and data visualization tools. These provide sharper insight into global trends than was previously available"--